PEDAGOGICAL OPPORTUNITIES FOR ORGANIZING INDEPENDENT EDUCATION IN PHILOSOPHY - Samatov, Dilshodbek Toxirjonovich (Educational Research in Universal Sciences, 2023)
This article will talk about issues related to the application of advanced pedagogical technologies in the process of teaching philosophy in the pedagogical higher education system of our country and their solution. Alternatively esse, its forms, conditions of writing condition, structure and importance.